A practical approach to multi-modeling views composition - Yie, Andres; Cassallas, Rubby; Deridder, Dirk; Wagelaar, Dennis (Electronic Communications of the EASST, 2009)
The use of several view models to specify a complex system is a common practice to provide the most appropriate abstractions to model its diverse concerns. When several view models are used to specify a system, it is necessary to compose them to generate the application. When the view models are expressed in different Domain Specific Modeling Languages a problem arises because a heterogeneous composition is required. A possible approach to avoid a heterogeneous composition is to transform the diverse models into low-level models using a common low-level modeling language as target. Therefore, when all the view models are transformed in low-level models specified with a common language, it is possible to apply a ho- mogeneous composition to obtain the final application. However, it is necessary to identify the elements to compose in the low-level. In this paper, we present an auto- matic mechanism to identify which elements will be composed. This mechanism is based on defining correspondence relationships between the high-level view mod- els and automatically deriving new correspondence between the generated low-level models.